Supposition about absence of contact inhibition of cancer cells - Gogichadze G; Gogichadze T; Mchedlishvili E (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2021)
As is known, the superficial charge of most somatic cells is negative. Proceeding from this fact, somatic cells never interact. There is always some type of space (intercellular space) between them. Intercellular contacts are predominantly determined by two main factors: Van der Waals (positive taxis) and electrostatic (negative taxis) forces contributing to the formation of membrane electric potential. Presence of the intercellular space is a structural representation of the balance between these forces (contact inhibition).